68 A Full Audit Cycle: Documentation of Discharge Summaries and Functional Status in Electronic Discharge Letters. (16th March 2021) - Mir, A; Damany, S; Tay, H S
Abstract: Introduction: Electronic discharge letter is the most effective way to handover to General Practitioners for the continuity of care by providing the information about what happened during hospitalisation and what needs to happen after discharge. Well written discharge letters prevent miscommunication, missing information and medications errors as well as reduction of hospital workload. It also provides timely follow up to decrease the risk of re-hospitalisation. The aim of this project is to analyse the documentation of discharge summaries and functional status after hospital admission in discharge letters. Discharge summary template was introduced and made compulsory in all Geriatric wards following first cycle of audit. We then compared data after introduction of discharge summary template. Methods: Electronic discharge letters were reviewed for all patients discharged from Geriatric Department in July 2019 and results were compared with data from January 2019. Results: 162 patients were discharged in the second cycle of audit. Among these, 18 patients were deceased, and 4 patients had no discharge letters available. Therefore, total number of discharge letters analysed was 140. Please see Table 1 for comparative results on documentation of discharge summaries in discharge letters. Conclusions: Introduction of the discharge summary template improved the documentation of summaries in discharge letters. Well-written discharge letter ensures the smooth transition for when patients leave the hospital. Therefore, it should be accurate, precise and relevant.